2007
DOI: 10.1271/bbb.60562
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Polyphenols from Oolong Tea and Black Tea: Purification, Some Properties, and Role in Increasing Mitochondrial Membrane Potential

Abstract: High-molecular-weight polyphenols from oolong and black teas increased mitochondrial membrane potential, as measured by a method using ciliated protozoan Tetrahymena and rhodamine 123. These polyphenols, referred to as mitochondrial activation factors (MAFs), were purified from oolong and black teas by solvent extraction and Toyopearl column chromatography. The number-average molecular weights of the MAFs were 9,000 to 18,000, and the weight-average molecular weights were 15,000 to 25,000. The MAFs increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
(35 reference statements)
0
35
0
Order By: Relevance
“…MAF was derived from a fraction strongly increasing the mitochondrial membrane potential in T. pyriformis. MAF prepared from a pH 3.0 butanol fraction 4) and that from a pH 2.0 butanol fraction showed the same properties, including effects on mitochondrial membrane potential and elution profiles on Toyopearl HW-40F column chromatography and HPLC with an ODS column. MAF was dissolved in DMSO, and 10 mg/mL of MAF in 0.1% DMSO was prepared with ASW.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…MAF was derived from a fraction strongly increasing the mitochondrial membrane potential in T. pyriformis. MAF prepared from a pH 3.0 butanol fraction 4) and that from a pH 2.0 butanol fraction showed the same properties, including effects on mitochondrial membrane potential and elution profiles on Toyopearl HW-40F column chromatography and HPLC with an ODS column. MAF was dissolved in DMSO, and 10 mg/mL of MAF in 0.1% DMSO was prepared with ASW.…”
mentioning
confidence: 79%
“…We examined the effects of MAF on mitochondrial respiration by measuring mitochondrial membrane potential using 10 mM rhodamine 123. 4) Localization of rhodamine 123 fluorescence to the midpiece of the sea urchin sperm suggested that this is where the mitochondria are located ( Fig. 2A-C).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…According to the chemiosmotic theory, measuring mitochondrial inner-membrane potential (ΔΨ m ) has been used as an index of mitochondrial activity because ΔΨ m is utilized to provide energy for ATP production (Solani et al 2007 ). Mitochondrial activation is believed to be by changes in hyperpolarization of ΔΨ m (Fujihara et al 2007 ). On the other hand, ΔNO at fertilization has been reported in sea urchin eggs, although its main function is still obscure (Leckie et al 2003 ;Mohri et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%